The use of part-time faculty in associate degree nursing, social science, and biological science programs. - Shepard PA (Use of Part-time Faculty in Associate Degree Nursing, Social Science & Biological Science Programs, 1990)
This study surveyed the opinions of academic administrators of associate degree nursing programs, community college social science programs, and community college biological science programs regarding major benefits and concerns associated with the employment of part-time faculty. This study found that most part-time social science faculty teach in the classroom, half participate in non-teaching faculty activities, and most are paid a contract amount per course or credit hour. Part-time biological science faculty differed only in that most teach a combination of classroom and lab/practicum. Part-time nursing faculty differed in all three areas. Most part-time nursing faculty teach in lab or practicum settings, most participate in more non-teaching activities than other part-time faculty, and most are paid an hourly wage. However, the benefits and concerns associated with the employment of part-time nursing faculty were not significantly different from those identified by academic administrators of the other programs with one exception. Academic administrators felt that part-time nursing faculty expose students to the latest technologies in specialty areas and part-time social science faculty do not. The benefits cited by the respondents, that were in addition to the benefits most frequently cited in the literature, include increased interaction with the community and the ability to 'try out' prospective full-time faculty. The concerns cited by respondents, that were in addition to the concerns most frequently cited in the literature, include the inability to find qualified part-time faculty to fill available positions and the concern that the employment of part-time faculty causes resentment among full-time faculty. The results from this study indicate that the literature pertaining to the benefits and concerns associated with the employment of social science and biological science part-time faculty in community colleges can be used to develop policies regarding part-time faculty in associate degree nursing programs.